2005
DOI: 10.1002/jcp.20424
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell‐cycle regulators in lung cancer

Abstract: Lung cancer is the leading cause of cancer death worldwide. Histologically, 80% of lung cancers are classified as non-smallcell lung cancer (NSCLC), and the remaining 20% as small-cell lung cancer (SCLC). Lung carcinoma is the result of molecular changes in the cell, resulting in the deregulation of pathways controlling normal cellular growth, differentiation, and apoptosis. This review summarizes some of the most recent findings about the role of cell-cycle proteins in lung cancer pathogenesis and progression. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 81 publications
(82 reference statements)
1
19
0
Order By: Relevance
“…In this study, the effects of aerosol-delivered PDCD4 on cell cycle control in lungs of K-ras null mice were investigated. Initiation of cell cycle control via extracellular signals induces the transcription of several proteins, including cyclin D, which, when complexed with cyclin-dependent kinase 4, moves into the next cell cycle (30). In our study, aerosol-delivered PDCD4 may regulate lung cancer growth through increasing the cell cycle inhibitors, such as p21 and p27, while suppressing cell proliferation proteins, such as cyclindependent kinase 4 and proliferating cell nuclear antigen (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, the effects of aerosol-delivered PDCD4 on cell cycle control in lungs of K-ras null mice were investigated. Initiation of cell cycle control via extracellular signals induces the transcription of several proteins, including cyclin D, which, when complexed with cyclin-dependent kinase 4, moves into the next cell cycle (30). In our study, aerosol-delivered PDCD4 may regulate lung cancer growth through increasing the cell cycle inhibitors, such as p21 and p27, while suppressing cell proliferation proteins, such as cyclindependent kinase 4 and proliferating cell nuclear antigen (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the effect of aerosol-delivered PDCD4 on p53 was insignificant. However, cell growth may be regulated by p53 target gene p21 because some research reports showed that p53 could bind to specific DNA sequence and transactivate a group of target genes, including p21, thereby inhibiting cell proliferation and promoting apoptosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…This is also due to the initial observations suggesting that RB family proteins have overlapping functions. However, several studies have evidenced functional differences among these proteins (Claudio et al, 1994;Hurford et al, 1997;Jori et al, 2004;Caputi et al, 2005). In this review, we will focus only the differences in regulation of stem cell biology.…”
Section: Rb and Hematopoiesismentioning
confidence: 99%
“…Constitutive activation of cyclin E/cdk2 complexes has been often associated with G 1 /S deregulation and tumor progression (Harwell et al, 2004;Liao et al, 2004;Sunters et al, 2004). Among the target substrates that cdks phosphorylate are the members of the retinoblastoma (Rb) family proteins, which play a pivotal role as negative regulators of cell cycle progression (Claudio et al, 1994;Caputi et al, 2005;Gallo and Giordano, 2005). This family includes the product of the Rb susceptibility gene, the pRb/p105 protein and the related p107 and pRb2/130 proteins (Mayol et al, 1993;Du and Pogoriler, 2006;Merola et al, 2006).…”
Section: Introductionmentioning
confidence: 99%